Slightly Regular Measures and Measureable Sets - James Camacho (Journal of Mathematics)
Outer and inner measures of a measure μ are defined and used to prove results involving them on a lattice l and its complement l′. The results concern slightly regular measures and sets such as Sμ which is the collection of μ-measureable sets.